La Libertà di manifestazione del pensiero e la libertà religiosa nelle società multiculturali - LOPRIENO, Donatella; Fiorita, Nicola (Atti, 2009)
The balancing of rights of equal status is a question widely debated in all modern legal systems, but the complexity of western societies – increasingly engaged with the interaction of different cultures and traditions – expands its quantitative and qualitative significance immeasurably. The purpose of this book is to appraise the potential intersection between two values that are crucial in every community: religious freedom and freedom of intellectual expression. Specialists in various areas of legal science have been asked to make their contributions on this question, the result of which is a precious mapping of the open issues, convincing solutions and suggestions generated by other legal experiences, in addition to the weaknesses that undermine the legal system in force